Pupil responses to intravenous heroin (diamorphine) in dependent and non-dependent humans. - Tress, K H (1979)
1. Intravenous heroin was administered to volunteers, in doses of 2.5 and 5 mg to non-dependent subjects and does of 1/6, 1/3 and 1/2 of their prescribed daily does of opiates to dependent subjects, and pupillary responses measured before and three times during the 2 h after injection. 2. Tolerance to the miotic effects of heroin in the dependent subjects was demonstrated--larger doses of heroin were needed to produce the same pupil response in dependent subjects than in non-dependent subjects and the duration of action was shorter in the former group. 3. The effect of concurrent oral methadone medication on pupil response to heroin was demonstrated. Subjects prescribed both methadone and heroin showed smaller control pupil diameters and a reduced dose effect to heroin than did subjects prescribed heroin alone.